(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: In recent years, obesity significantly increased in all the age groups due to sedentary lifestyle. It can result into chronic heart disease. So walking is very beneficial for every individual therefore this study is aimed to compare the effect of Nordic and Normal walking on coronary risk factor in middle aged obese population. 32 middle aged obese individuals were participated in this study they were divided into 2 group. One group performed Nordic walking and other Normal walking and evaluate the efficiency of Nordic and Normal walking for the coronary risk factor. Objective: To assess the W-H Ratio BMI, HDL and LDL level To find out the pre and post effect of Nordic and normal walking on the coronary risk factors. Methodology: The study subjects were 32 middle aged obese individuals. They were divided into 2 groups. The primary intervention to Group A consist of a Nordic Walking and Normal walking for group B. Individuals were selected according to inclusion criteria age between 45-65 years, Body Mass Index ?30 kg/m2 , Waist – Hip Ratio > 0.9 cm for men and 0.8 cm in female, HDL < 40mg/dL, LDL > 130 mg/dL and exclusion criteria was individuals taking medication which influence the variable measured, any orthopedic condition that limit the exercise, unstable angina, uncontrolled hypertension – SBP ? 200 mmHg and DBP ?110 mmHg. Result: Statistical analysis for BMI, Waist – Hip ratio, LDL and LDL level was significant (P value = 0.0001) in individuals performed Nordic walking. In normal walking P value is changes in BMI, W-H ratio, HDL and LDL level which was not significant. Conclusion: From this study, it can be concluded that the Nordic walking reduces the coronary risk factor in middle aged obese population than the normal walking.